Moral Education And The Independence Of Students In Boarding Schools Al-Urwatul Wutsqo Jombang - Desy Naelasari (STAI Miftahul Ula Nganjuk, 2018)
Boarding school as an educational institution to do various things, one of them in moral education. In Pondok Pesantren Al-Urwatul Wutsqo example of moral education is, all young students who are required to kiss the hands of older, in addition to the students if paying respect to the cleric, said district, class, name. In addition to moral educated, well educated independence. Independence in question is not spoiled the students are educated, competent, and can be in any field or ready to take life in the community. Data collection techniques using observation, interviews, and documentation. Data analysis included data reduction, data display, and verifying conclusion. Test the validity of the Data through an extension of the participation, persistence observers and triangulation. The study resulted in Conclusions: 1) moral education of students through formal and informal education in PP-UW, a form of education more priority to physical education than the education of the soul first. Phase-stage is done by coercion roommates Gradually no longer feels forced. 2) Education independence of students through formal and informal education in PP-UW Dare to Compete audiences teach students how to conduct interaction and not depend on others, Teaches pious charity so that students are not saturated, self-contained and ready to face the future in public life. 3) The factors supporting and morals of students items, namely internal and external factors. Internal factors that students have the will to be educated character, each input students are different, and so on. The external factor is the existence of subjects Quran, teachers at school, the school environment that is outside and figures that play a role. 4) Factors supporting and independence of students: (a) the pattern of parenting. (B) The system of life-UW School MA. (C) System of life in the hut.